Mucinous cystic neoplasm of pancreas a case report - V., Neetha; Joe, Anuroop; S., Hanumanthaiah K.; S., Venkatesh (International Surgery Journal, 2021)
Mucinous cystic neoplasm of pancreas are relatively rare >95% occur in the body and tail of pancreas. Majority occur in young and middle aged female containing ovarian type subepithelial stroma. These tumors are either premalignant (MCN with low grade dysplasia) or (MCN with high grade dysplasia) or invasive carcinoma. Differential diagnosis includes pancreatic pseudocyst and pancreatic hydatid cyst. Investigations include ultrasonography (USG), Magnetic resonance imaging (MRI), Contrast enhanced computed tomography (CECT) supplemented by endoscopic USG with cyst fluid aspiration.